Ventricular septal defect in children born in Liverpool 1960 to 1969. Evaluation of natural course and surgical implications in an unselected population. Issue 1 (July 1981) - Dickinson, D F; Arnold, R; Wilkinson, J L
Abstract : We have reviewed data on all patients born between 1960 and 1969 and registered in the Liverpool Registry of Congenital Malformations as having congenital heart disease. There were 385 with a ventricular septal defect as their sole or main cardiac lesion. Analysis of the available follow-up data showed that 50 of these were subsequently assigned in other diagnostic categories and a further 41 failed to fulfil our diagnostic criteria for a ventricular septal defect, leaving 294 patients for study. In view of the high incidence of small defects in asymptomatic infants and children not subjected to cardiac catheterisation, clinical criteria for the acceptance of the diagnosis were defined and 190 patients were included on these grounds alone. The clinical course, associated cardiac and non-cardiac defects, and surgical implications were analysed. The majority of defects were small and 31% closed spontaneously. Fifty per cent of the deaths in infancy were unrelated to the ventricular septal defect. We estimate that by present criteria only 15% of an unselected population of patients with a ventricular septal defect are likely to require surgical treatment.